Fear of death: everyday experience-based nurses ’observations in working with elderly and old patients ill with chronic cardiovascular diseases - Kristina Bulkina; Vilma Žydžiūnaitė (Taikomieji Moksliniai Tyrimai)
Summary Fear of death occurs when elderly and old patients (EOPs) are faced with life-threatening events or extreme psychological stress. For most, anticipation of death triggers negative emotions such as the fear of losing of oneself, helplessness, and a loss of control. Fear of death is one of the most prevalent psychiatric consequences of chronic health conditions. Nurses face challenges in caring for EOPs ill with chronic cardiovascular diseases (CCVDs) snd this is related to high emotional stress and fatigue associated with constant monitoring of patients and managing their anxiety and fears. Fear of death is a common concern among EOP with CCVDs. There is relatively little research that examines the relationship between EOPs ’CCVDs and experienced fear of death phenomena from the perspective of nurses. Research question, to which the answer was sought was ‘How do nurses de scribe the symptoms, signs of fear of death among EOPs ’ill with CCVDs and how they recognise the features of patients ’fear of death?’ A total of 15 nurses had participated in the study. Data were collected by using semi-structured interviews. The manifest qualitative content analysis for data anal ysis were applied. Findings revealed that the related emotional/psychological, physiological and be havioural changes were observed by nurses and the characteristics for recognising the feeling of death in patients were identified. Characteristics of EOPs ill with CCVDs and experiencing fear of death are related to changes in emotions, behaviour and physical/physiological symptoms/signs that are interrelated with their emotional state. The social, spiritual and creative needs of patients are intensi fied while they experience fear of death.